2009
DOI: 10.1007/s00405-009-0996-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of extracellular matrix proteins in ameloblastomas and adenomatoid odontogenic tumors

Abstract: This study evaluated the expression of Wbronectin, tenascin and type I collagen in ameloblastomas and adenomatoid odontogenic tumors (AOTs) aiming to contribute with the comprehension of the diVerences in the biological behavior of these tumors. Immunohistochemical technique was performed in 20 cases of ameloblastoma (16 solid and 4 desmoplastic) and in 10 cases of AOT. All tumors presented moderate Wbronectin expression in the stroma. Solid ameloblastomas showed intense expression of Wbronectin at the epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…The extracellular matrix might also influence this finding as MCs have a high affinity for the adsorption to fibronectin induced by stem cell factor (SFC) or from integrin receptors [22][23][24]. In addition, several researchers have reported the presence of fibronectin in the extracellular matrix of OTs [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular matrix might also influence this finding as MCs have a high affinity for the adsorption to fibronectin induced by stem cell factor (SFC) or from integrin receptors [22][23][24]. In addition, several researchers have reported the presence of fibronectin in the extracellular matrix of OTs [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Positive reactions were observed for amelogenin, laminin, heparan sulfate proteoglycan (HSPG), collagen types I and IV, tenascin, fibronectin, and osteonectin [34][35][36][37][38] . In these studies, strong stainings have been reported in limited areas of AOTs, especially in the matrix of immature enamel present in duct-like structures and hyaline droplets, but the nature of amorphous eosinophilic material of AOTs is a matter of discussion: a dystrophic enamel-like tissue produced by neoplastic epithelial basal cells, 28 real enamel tissue, 39 or dentinoid tissue with ectomesenchymal component 40 have been evocated.…”
Section: Extracellular Matrix (Ecm) Components and Metalloproteinasesmentioning
confidence: 99%
“…MMP and tenascin expression in odontogenic lesions have been shown in a few studies previously (4)(5)(6). Still, the relationship between MMP and tenascin expression and the biological behavior of odontogenic lesions has not yet been identified.…”
Section: Ameloblastomamentioning
confidence: 99%